Diagrams of Power : Visualizing, mapping, and performing resistance - Davila, Patricio ([S.l.] : Onomatopee, 2019)
Akers, Joshua ; The Anti-Eviction Mapping Project ; Arikan, Burak ; Begley, Josh ; Beuys, Joseph ; Davila, Patricio ; Bureau d'Études ; Department of Unusual Certainties ; D'Ignazio, Catherine ; W.E.B. Du Bois ; Esudio Teddy Cruz + Fonna Forman ; Forensic Architecture ; Terra Graziani ; Hill, Alex ; Iconoclasistas ; LaRochelle, Lucas ; Laxness, Stefan ; Mehretu, Julie ; Macdonald, Eliana ; Mogel, Lize ; Mikana, Ogimaa ; Pearce, Margaret ; Poitras, Laura ; Rekacewicz, Philippe ; Sampath, Sheila ; Visualizing impact
boek